Die funksie en waarde van agtergrondstudie van die Nuwe Testament - A.B. du Toit (Verbum et Ecclesia, 1995)
Background study of the New Testament: its function and value To be able to understand any nonnal linguistic utterance, infonnation regarding the context within which it functions, is of decisive importance. For that reason every exegete of the New Testament has to develop a broad frame of reference regarding the Jewish and Graeco-ROInan world within which the New Testament documents originated. In spite of various obstacles, our knowledge of that world has increased immensely over the last century. The exegete should, however, also carefully distinguish between textual world, which is a construct of the author, and real world. As illustration of the value of background knowledge Romans 13:1-7 is discussed. It seems that both anti-ROInan tendencies in Palestine and dissatisfaction with the ROInan taxation system led to Paul's admonitions in this passage. It is also shown how several details of the text become transparent in the light of background infonnation. The danger inherent in accentuating background study at the cost of the text itself is also illustrated.